Disability Scholarship Impact Evaluation - Maghfira, Rizkyta Cahya; Wisesa, Victo Anggara (Graduate Program Magister Manajemen Pendidikan, 2025)
This study explores the transformative potential of the Disability Scholarship Program initiated by Indonesia’s Ministry of Finance through the Indonesia Endowment Fund for Education (LPDP) in 2019. The program aims to empower persons with disabilities by providing access to higher education. A qualitative approach was adopted, combining semi-structured interviews and questionnaires using a four-point Likert scale. Data were analyzed through thematic analysis, integrating both primary and secondary sources. Findings indicate that the program successfully facilitates access to top universities (mean score: 3.80), enhances equal opportunity (3.75), and enables alumni to inspire others in their communities (3.85). These outcomes highlight the program’s broader social impact beyond educational access. Based on the results, the study proposes practical improvements, including regular policy updates, professional assistance during recruitment, customized academic and psychological preparation, stronger monitoring, active alumni engagement, and comprehensive staff training. These recommendations aim to strengthen the program’s inclusivity and sustainability. This study offers a new perspective by evaluating the LPDP disability scholarship from the beneficiaries’ viewpoint and providing actionable, field-based recommendations to inform inclusive scholarship policies.